2013
DOI: 10.5665/sleep.2806
|View full text |Cite
|
Sign up to set email alerts
|

Nightmares: Prevalence among the Finnish General Adult Population and War Veterans during 1972-2007

Abstract: Sandman N; Valli K; Kronholm E; Ollila HM; Revonsuo A; Laatikainen T; Paunio T. Nightmares: prevalence among the Finnish general adult population and war veterans during 1972-2007. 2013;36(7):1041-1050.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
100
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(111 citation statements)
references
References 43 publications
9
100
1
1
Order By: Relevance
“…In agreement with previous studies, we found that the dream anxiety level of females was higher than that of males (24,25,26). Several factors might explain why females have more dream anxiety compared with males, including higher rate of dream recall frequency in females, greater vulnerability to depression, more frequent childhood trauma history, and lower androgen levels, all of which have been reported to attenuate sympathetically mediated components of the integrated central stress response (25,27,28,29,30).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In agreement with previous studies, we found that the dream anxiety level of females was higher than that of males (24,25,26). Several factors might explain why females have more dream anxiety compared with males, including higher rate of dream recall frequency in females, greater vulnerability to depression, more frequent childhood trauma history, and lower androgen levels, all of which have been reported to attenuate sympathetically mediated components of the integrated central stress response (25,27,28,29,30).…”
Section: Discussionsupporting
confidence: 81%
“…Several factors might explain why females have more dream anxiety compared with males, including higher rate of dream recall frequency in females, greater vulnerability to depression, more frequent childhood trauma history, and lower androgen levels, all of which have been reported to attenuate sympathetically mediated components of the integrated central stress response (25,27,28,29,30). People who suffer from nightmares can become lucid in their dreams by performing daily exercises (31).…”
Section: Discussionmentioning
confidence: 99%
“…12 The findings that nightmare frequency decreases with age and women tend to report more nightmares are in line with previous population-based German samples 2,21,22 and a large sample of patients with sleep disorders, 12 thus supporting the validity of the present findings. It has to be noted that the findings regarding the decrease of nightmare frequency with age conflicts with some studies, 21,23 but the gender difference is well-documented. 24 The percentage of individuals with frequent nightmares having sought professional help (33%) is also in line with previous studies, [13][14][15][16] but interestingly, a considerable number of patients consulting a sleep clinic and suffering from nightmares have asked psychotherapists/psychologist for help-in contrast to the findings of an online study of nightmare sufferers of whom none consulted a psychologist.…”
mentioning
confidence: 40%
“…[3][4][5][6][7][8][9] In the largest study to date (69,813 adults), the prevalence of nightmares was 3.5% in men and 4.8% in women. 10 Participants from the World War II generation had a significantly higher prevalence of 7.2% in men and 7% in women. Nightmares are more common among patients with sleep disturbances, sleep disorders, depression, anxiety, and posttraumatic stress disorder However, most research evaluating sleep disorders in active duty military personnel has focused on insomnia, obstructive sleep apnea (OSA), and PTSD, noting that a recent study focusing on OSA and PTSD did not evaluate nightmares.…”
Section: Introductionmentioning
confidence: 98%
“…24,25 Research on nightmares in military personnel is limited, though data suggest that veterans who have left military service have a higher prevalence than the general population. 10 The primary objective of this study was to characterize the prevalence of nightmares in United States military personnel with sleep disturbances. The secondary objective was to describe the clinical and polysomnography (PSG)-measured correlates of military personnel with nightmares.…”
mentioning
confidence: 99%